Association between Serum 8-Iso-Prostaglandin F2α as an Oxidative Stress Marker and Immunological Markers in a Cohort of Preeclampsia Patients - Lidia Boldeanu; Constantin-Cristian Văduva; Daniel Cosmin Caragea; Marius Bogdan Novac; Mariana Manasia; Isabela Siloși; Maria Magdalena Manolea; Mihail Virgil Boldeanu; Anda Lorena Dijmărescu (Life, 2023)
Background: We aimed to analyze the presence and clinical use of serum 8-iso-prostaglandin F2-alpha (8-iso-PGF2α) as an oxidative stress marker and some inflammatory status biomarkers (tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL-6), IL-10, high-sensitivity C-reactive protein (hs-CRP), and pentraxin-3 (PTX3)) for patients with preeclampsia (PE). Methods: Sixty pregnant women, including thirty diagnosed with PE and thirty who were healthy (NP), were included in this study. For the assessment of serum levels of biomarkers, we used the Enzyme-Linked Immunosorbent Assay (ELISA) technique. Results: Our preliminary study showed that the expression level of serum 8-iso-PGF2α in the PE group was higher than in the PE after delivery (PE-AD) group (742.00 vs. 324.00 pg/mL, p < 0.0001). Groups of preeclamptic patients (PE + PE-AD) expressed significantly elevated levels for all of the assessed inflammatory mediators as compared to NP. Significant strong positive correlations with 8-iso-PGF2α levels were found for systolic blood pressure (SBP), and TNF-α (Spearman’s rho = 0.622, p-value = 0.020 and rho = 0.645, p-value = 0.002, respectively). Our study demonstrates that 8-iso-PGF2α and PTX3 have the greatest diagnostic value for pregnant women with PE. Conclusions: 8-iso-PGF2α and PTX3 can be used as independent predictor factors, along with already-known cytokines, that could represent a prophylactic way to help clinicians identify or predict which pregnant women will develop PE.